Analysis of steady‐state and transient thermal properties of cermet, polymer and LTCC thick‐film resistors. (2014) - ,; ,; ,; ,; ,
Abstract : Purpose – The purpose of this paper is to present the results of thermal analysis of cermet resistors made on alumina or LTCC substrate and polymer thick‐film resistors embedded in FR‐4 substrate.Design/methodology/approach – The study was performed using a thermal imaging method. The research was carried out with an additional consideration of such factors as sheet resistance (which depended on the type of resistive paste), the size and topology of element and the kind of contact material (Cu, Ag or Ni/Au). A few key points on the element were specified for which a more thorough analysis was carried out. The results were approximated by physically acceptable function which allowed to determine the influence of different mechanisms of heat transfer and determine their time and thermal constants.Findings – The effectiveness of heat dissipation from resistor is determined by the type of substrate material, width of conductive paths, and contact material. The best results were observed for elements with wider conductive paths made of Cu or Ni/Au. The LTCC substrate ensures the fastest achieving of stable temperature on the component. The changes of the temperature gradient in time can be described by a formula consisting of two or three exponent parts, each one presenting different mechanism of change.Research limitations/implications – These studies do not include more detailed determination of nature of found mechanisms of change. There has not also been established what form of the formula is more accurate physically description of the results for respective structure.Originality/value – The results provide important data of the thermal properties of the chosen materials. This allows to determine their usability for specific applications where heat distribution plays an important role. The used analysis method is proven to provide reliable results and can be considered to be used for further studies in that subject. Acknowledgements : This work was supported by the National Science Centre (Poland), Grant DEC‐2011/01/B/ST7/06564.